Francesca Ferrando, Philosophical Posthumanism - Dedeoğlu, Çağdaş (Journal for the study of religion, nature and culture, 2021)
Francesca Ferrando, Philosophical Posthumanism (London et al.: Bloomsbury Academic, 2019), 296pp., $103.50 (pbk), ISBN: 978-1-3500-5950-4.